The Integrated Excel Based K3 Recording System for Occupational Incident Monitoring - Dewi Agustina; Laura Natalia Christin Sinuraya; Juliani; Istifani Nasution; Rika Iyut Tira; Elisa Apriani; Siti Khodiza Sihombing; Ahmad Fitrah Raihan (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to develop and implement an integrated Microsoft Excel based recording system to improve the accuracy and efficiency of reporting Occupational Accidents and Occupational Diseases in a lung specialized hospital. The research used an action research approach involving stages of problem identification, system design, staff training, implementation, and evaluation. The integrated Excel Planner was designed to standardize incident documentation, enhance data completeness, and accelerate reporting processes. The results showed a significant improvement in reporting speed, reducing reporting time from an average of three days to one day. Data completeness also increased from 65% to 95% after system implementation. Features such as filters, pivot tables, and graphs supported analytical activities, including identifying high risk areas and determining root causes of incidents. The findings indicate that a simple digital solution like Excel can strengthen the hospital’s occupational safety system and support more effective decision making. The success of this system was influenced by participatory planning and active staff involvement. Continuous updates and further integration with hospital information systems are recommended to maintain system sustainability.